2007
DOI: 10.1264/jsme2.22.44
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Tetracycline Resistance Genes in Bacteria Isolated from Various Agricultural Environments

Abstract: A total of 350 tetracycline-resistant (Tc r ) bacteria were isolated from livestock feces, farmyard manure (FYM), and soil in Japan. The isolates were classified into 28 established genera of the phyla Actinobacteria, Bacteriodetes, Firmicutes and Proteobacteria by studying partial 16S rRNA gene sequences. PCR analysis revealed that 249 of the 350 Tc r isolates contained at least 1 of 15 Tc r genes (tet genes): 140 isolates contained an efflux pump gene and 109 isolates contained a ribosomal protection protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 22 publications
1
24
1
2
Order By: Relevance
“…TC-r genes are commonly associated with mobile genetic elements such as integrons, transposons and plasmids, which allow for their spread to unrelated bacteria, including those from different environmental niches (Chopra and Roberts, 2001;Forsberg et al, 2012). Indeed, virtually the same TC-r genes were found in soil, manure and humans (Kobashi et al, 2007;Forsberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…TC-r genes are commonly associated with mobile genetic elements such as integrons, transposons and plasmids, which allow for their spread to unrelated bacteria, including those from different environmental niches (Chopra and Roberts, 2001;Forsberg et al, 2012). Indeed, virtually the same TC-r genes were found in soil, manure and humans (Kobashi et al, 2007;Forsberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In enterococci, two major groups of tetracycline resistance genes have been identified. The first group include tet(M), tet(O) and tet(S) genes that encoding ribosomal protection proteins, and the second group encodes tetracycline efflux pumps proteins by the tet(L) and tet(K) genes (Chopra and Roberts 2001;Huys et al 2004;Poeta et al 2005;Kobashi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While only 39 genera carried these genes in 2001, the number rose to 115 in 2005 (28). In 2007, Kobashi et al identified 13 other new genera that were determined to carry tetracycline genes, and Macauley et al found 5 other new genera that carry tetracycline efflux genes (29,30). We found 2 new genera that were identified for the first time as carrying the tet(C) gene.…”
Section: Discussionmentioning
confidence: 65%